Nesting Habitat of Greater Adjutant Stork - Changkakati, H. C.; Das, R. K. (Indian Forester, 1991)
The Greater Adjutant Stork (Leptoptilos dubius) is fast becoming endangered and only Assam harbours a meagre population of around 500. Till now only 99 nests have been recorded in Assam. The breeding period of the bird is the winter and 2 to 3 eggs are laid by the female. The bird is a carrion feeder and during rainy season when the water-table is high in the marshy places they are found feeding garbage. Local Forest Officers are taking due interests in making the people aware of protecting the nesting sites which are particularly in the private lands.